The Incidence of Propofol-Induced Hypertriglyceridemia and Identification of Associated Risk Factors - Corrado, Michael J. (Crit Care Explor, 2020)
OBJECTIVES: The objective of this study was to describe the incidence of propofol-induced hypertriglyceridemia and the risk factors associated with hypertriglyceridemia in mechanically ventilated ICU patients while receiving propofol. DESIGN: This was a single-center case-control study. SETTING: Brigham and Women’s Hospital, a tertiary academic medical center in Boston, MA. SUBJECTS: Adult ICU patients who received continuous infusion propofol for at least 24 hours from May 1, 2019, to December 31, 2019, were included. Patients were excluded if they were diagnosed with acute pancreatitis upon admission or did not have any serum triglyceride levels evaluated during propofol administration. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: The major outcome was the incidence and risk factors associated with the development of propofol-induced hypertriglyceridemia, defined as triglyceride level greater than or equal to 400 mg/dL. Minor outcomes included the prevalence of acute pancreatitis. A hybrid multivariate logistic regression analysis was used to evaluate the relation between individual risk factors and the dependent variable of hypertriglyceridemia. During the study period, 552 patients were evaluated for inclusion, of which 136 were included in the final analysis. A total of 38 patients (27.9%) developed hypertriglyceridemia with a median time to hypertriglyceridemia of 47 hours. The only significant independent risk factor for development of hypertriglyceridemia identified was the cumulative propofol dose (odds ratio, 1.04; 95% CI, 1.01–1.08; p = 0.016). Two of the 38 hypertriglyceridemia patients (5.3%) were diagnosed with acute pancreatitis. CONCLUSIONS: In our analysis, approximately one third of patients developed hypertriglyceridemia with cumulative propofol dose identified as a significant predictor of the development of hypertriglyceridemia. Despite a high incidence of hypertriglyceridemia, a significant number of patients continued propofol therapy, and a relatively low prevalence of pancreatitis was observed. Future analyses are warranted to further investigate these results.